2014
DOI: 10.1097/ogx.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Surgery

Abstract: In utero fetal surgery interventions are currently considered in selected cases of congenital diaphragmatic hernia, cystic pulmonary abnormalities, amniotic band sequence, selected congenital heart abnormalities, myelomeningocele, sacrococcygeal teratoma, obstructive uropathy, and complications of twin pregnancy. Randomized controlled trials have demonstrated an advantage for open fetal surgery of myelomeningocele and for fetoscopic selective laser coagulation of placental vessels in twin-to-twin transfusion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(2 citation statements)
references
References 89 publications
0
1
0
1
Order By: Relevance
“…Surprisingly, this study also identified novel genes and pathways differentially-regulated in fetuses with myelomeningocele that involve multiple distinct steps of spinal and neural development beyond neurulation processes, such as spinal cord ventral-dorsal axis development ( Wnt1 , Wnt5A , SKI, GPR37 29,30 ), neuronal differentiation, axonal development ( Wnt5A, ITPR1, PLCB3, PLCE1, ACAP1, SEMA5A , and DRAXIN 29,30 ), dorsal root ganglion development ( SEMA5A, NEUROD , and ZEB1 31 ), Schwann cell development, motor neuron survival, synapse formation and neuronal injury and repair (Table 3). Disturbances in formation of the cortico-spinal tract may explain how progressive motor impairment occurs in myelomeningocele.…”
Section: Discussionmentioning
confidence: 76%
“…Surprisingly, this study also identified novel genes and pathways differentially-regulated in fetuses with myelomeningocele that involve multiple distinct steps of spinal and neural development beyond neurulation processes, such as spinal cord ventral-dorsal axis development ( Wnt1 , Wnt5A , SKI, GPR37 29,30 ), neuronal differentiation, axonal development ( Wnt5A, ITPR1, PLCB3, PLCE1, ACAP1, SEMA5A , and DRAXIN 29,30 ), dorsal root ganglion development ( SEMA5A, NEUROD , and ZEB1 31 ), Schwann cell development, motor neuron survival, synapse formation and neuronal injury and repair (Table 3). Disturbances in formation of the cortico-spinal tract may explain how progressive motor impairment occurs in myelomeningocele.…”
Section: Discussionmentioning
confidence: 76%
“…Эту проблему частично решили немецкие врачи из Медицинского университета Бонна: они предложили закачивать в околоплодную жидкость углекислый газ, безвредный для плода. Благодаря такому подходу отпадает необходимость в замене околоплодных вод [35,95]. Современные методы визуализации также способны в полной мере обеспечить полный обзор для хирурга.…”
unclassified